BI tools to monitor KPIs in operations management - Silva, Sofia Cloé Morais da (2023)
Key performance indicators are crucial for decision-making and essential to quantify the efficiency and effectiveness of operations management. Nowadays, provided by information technologies, it is possible to gather large sets of data and estimates that help and support the acquisition and calculation of KPIs. Big Data enables companies to use data as a strategic asset for decision-making and create value through data analysis and integration into strategic and operational activities. This dissertation focusses on improving the monitorization of a KPI through BI tools. This KPI is from Carglass Portugal and has the goal of measuring conversion. In order to improve the monitorization of this KPI, an R Script was developed with the goal of improving data pre-processing and a Power BI dashboard was constructed with the aim of enhancing data visualization and data analysis, and consequently decision-making. The methodology adopted was action-research structured in two cycles: Data Pre-Processing and Dashboard Construction. The principal findings of this research conclude that, indeed, BI tools with different purposes can improve efficiency in daily tasks but also enhance and fasten decision-making.